What is going on? a systematic review on QoS scenarios - Khanjani, Atieh; Wan Ab. Rahman, Wan Nurhayati (Ess & Ess Research Publications, 2013)
Quality of Service (QoS) is a set of non-functional requirements that could enhance the adoption rate of web services. It is essential to consider the QoS requirements for web services in order to guarantee for quality of web services and attract more users. There are many QoS scenarios such as QoS computation, QoS evaluation, QoS specification, QoS prediction and QoS measurement. In this paper, we prepare a systematic review study to provide a broad vision of primary studies to researchers in QoS scenarios to find the gaps and give the overview to perform researches to fill in the gap. The study focuses on these five most usable digital libraries including the IEEE Explorer,Springer link, ISI web of Knowledge, Emerald, and Science Direct between 2001 and 2012. The result shows that there is an urgent need to do research especially in QoS prediction and QoS computation.